2017
DOI: 10.1097/brs.0000000000001647
|View full text |Cite
|
Sign up to set email alerts
|

Patient Priority Weighting of the Roland Morris Disability Questionnaire Does Not Change Results of the Lumbar Epidural Steroid Injections for Spinal Stenosis Trial

Abstract: Study Design Secondary analysis of Lumbar Epidural steroid injections for Spinal Stenosis randomized controlled trial data. Objective To re-evaluate whether outcomes for older adults receiving epidural steroid injections with or without corticosteroid improve after using patient-prioritized Roland-Morris Disability Questionnaire (RDQ) items. Summary of Background Data Epidural corticosteroid injections are commonly used to treat lumbar spinal stenosis symptoms, despite limited evidence for their effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, some other studies did not find any significant improvement in symptoms or quality of life after an ESI for the treatment of LSS [ 67 , 68 , 69 , 70 ]. Tran et al wrote a review regarding the nonsurgical treatment of LSS and concluded that the literature could provide only limited evidence to formulate recommendations pertaining to the nonsurgical treatment of LSS [ 71 ].…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, some other studies did not find any significant improvement in symptoms or quality of life after an ESI for the treatment of LSS [ 67 , 68 , 69 , 70 ]. Tran et al wrote a review regarding the nonsurgical treatment of LSS and concluded that the literature could provide only limited evidence to formulate recommendations pertaining to the nonsurgical treatment of LSS [ 71 ].…”
Section: Resultsmentioning
confidence: 97%
“…Old age was an independent risk factor for LSS and its relevant surgery, and cardiopulmonary insufficiency had always been the biggest obstacle to the operation of elderly patients. Most of the elderly patients are accompanied by chronic diseases such as hypertension, coronary heart disease and diabetes, which made the treatment situation complicated 19–21. The elderly’s energy status was gradually applied in clinical practice as an independent factor to predict the risk of surgery while the research on it was increasingly deep.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the elderly patients are accompanied by chronic diseases such as hypertension, coronary heart disease and diabetes, which made the treatment situation complicated. [19][20][21] The elderly's energy status was gradually applied in clinical practice as an independent factor to predict the risk of surgery while the research on it was increasingly deep. Although increasing decompression and fusion surgeries were applied to the treatment of LSS to minimize the potential risk of future spinal instability and deformity, the merits of various decompression methods were still controversial, and there was no evidence to show that a certain decompression method or range was the most effective.…”
Section: Studies Focused On Lssmentioning
confidence: 99%
“…The improved outcomes at 3 weeks were statistically significant but not considered to be of clinical importance. 63 A follow-up subgroup analysis 64 using patient-prioritised Roland-Morris Disability Questionnaire items did not change the results. A total 21.5% of patients in the glucocorticoid-lidocaine group and 15.5% in the lidocaine alone group reported one or more adverse events (p=0.08).…”
Section: Epidural Injectionsmentioning
confidence: 91%